The Legacy of Parental Divorce as an Adverse Childhood Experience on Emerging Adults - Presence, Jewel Christina (University of the Witwatersrand, Johannesburg, 2024)
The impact of parental divorce on children is well documented, yet there is a significant gap in literature regarding its long-term effects on emerging adults. This qualitative study addresses this gap by exploring how emerging adults narrate and make meaning of their experiences of parental divorce during childhood. The study aims to understand how emerging adults interpret their childhood experiences of parental divorce and how it has affected their emotional, psychological, and social development in emerging adulthood. The study uses Arnett’s theory of emerging adulthood and Erikson’s theory of psychosocial development as theoretical frameworks. Data was collected using semi-structured interviews with 11 emerging adults, aged 18 to 24 years, who experienced parental divorce during childhood. Reflexive thematic analysis was employed to analyse the data. Three overarching themes emerged from the study: (1) navigating interpersonal relationships, (2) developmental transitions and parental divorce impact; as well as (3) family dynamics and support shifts. Findings reveal that parental divorce, during childhood, has emotional implications, leading to maladaptive coping strategies, difficulties within the home environment, and challenges in forming secure attachments in emerging adulthood. Despite these hardships, participants demonstrated resilience and adaptability, often reinterpreting their experiences in a positive light as they navigated self- identity and emerging adulthood. The effects of parental divorce on emerging adults were deeply embedded in their individual experiences including how they related to their parents during their childhood. This study provides valuable subjective insights into the long-term impacts of parental divorce on emerging adults by presenting data derived from participants’ experiences and includes recommendations for future research and practical applications.
A research report Submitted in fulfillment of the requirements for the degree of Masters in Community- Based Counselling Psychology, In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Parental Divorce; Adverse Childhood Experiences; Emerging Adulthood; Reflexive Thematic Analysis; SDG-16: Peace, justice and strong institutions; SDG-17: Partnerships for the goals